MoO2 Nanospheres Synthesized by Microwave-Assisted Solvothermal Method for the Detection of H2S in Wide Concentration Range at Low Temperature - An, Fei; Mu, Shanjun; Zhang, Shucai; Xu, Wei; Li, Na; Wang, Haozhi; Wang, Shiqiang; Zhao, Chenyang; Feng, Junjie; Wang, Lin; Sun, Bing (Frontiers in Materials, 2021)
It is crucial to develop highly energy-efficient and selective sensors for wide concentration range of H2S, a common toxic gas that widely exists in petrochemical industries. In this work, MoO2 nanospheres with uniform dimension were rapidly synthesized by microwave-assisted solvothermal method, and were subsequently fabricated into H2S gas sensor. The MoO2 nanospheres-based sensor exhibited excellent response toward H2S with good linearity in a wide concentration range (10-240 ppm). Besides, this sensor presented low working temperature, good repeatability and selectivity against CH4, H2 and CO. The outstanding sensing performance results from the reaction between H2S and abundant chemisorbed oxygen introduced by oxygen vacancies of MoO2.This result indicates that MoO2 nanosphere synthesized by microwave-assisted solvothermal method is a promising sensing material for H2S detection.